Dreams, sleep quality, and collective trauma - Mento, Carmela (Poligrafi, 2023)
The aim of the current study was to explore the impact of the CoVID-19 out-break on the dreams of a group of Italian participants. a total of 403 individuals were recruited online through a cross-sectional survey on Moodle. The qualitati-ve content of their dreams was analysed using the Dream Interview (TKYDQ), a tool created by Bulkeley. In addition, the Pittsburgh Sleep Quality Index (PSQI) was used to assess the quantitative aspects of dreams. from the results of our stu-dy, three macro-categories of content in the participants' dreams were identified: 1) dreams with phobic content; 2) dreams with a persecutory theme and 3) “old normal” dreams. Moreover, some sleep-related difficulties such as problems falling asleep and mild clinical sleep disorders were identified in the sample. The pro-longed quarantine and the lifestyle adopted during the pandemic have intensely influenced our dream activities, and it seems that CoVID-19 has already entered our collective unconscious in a symbolic way and through the processing of images and scenes related to the epidemic. The study, therefore, aims to explore how cata-strophic events affect mental health, specifically sleep quality and dream content.
Keywords: collective trauma; COVID-19; dreams; kolektivna travma; pandemic; pandemija; sanje; sleep; spanec